Exploring The Effect of Discussion Based Learning in The Flipped Classroom on Physics Concept Mastery - Saputri, Mawarni; Evendi, Evendi; Jannah, Rouzatul (FKIP Universitas Lampung, 2025)
This study aims to determine the effect of the Flipped Classroom learning model through the discussion method in improving students' conceptual understanding in physics learning. The population in this study consisted of all 49 eleventh-grade students, divided into a control class and an experimental class. The instruments used in this study were test instrument (two tier test) and non-test instruments (observation sheet and student response questionnaires). Students categorized as having a